2015
DOI: 10.1155/2015/396414
|View full text |Cite
|
Sign up to set email alerts
|

Mild Type 2 Diabetes Mellitus Reduces the Susceptibility of the Heart to Ischemia/Reperfusion Injury: Identification of Underlying Gene Expression Changes

Abstract: Despite clinical studies indicating that diabetic hearts are more sensitive to ischemia/reperfusion injury, experimental data is contradictory. Although mild diabetes prior to ischemia/reperfusion may induce a myocardial adaptation, further research is still needed. Nondiabetic Wistar (W) and type 2 diabetic Goto-Kakizaki (GK) rats (16-week-old) underwent 45 min occlusion of the left anterior descending coronary artery and 24 h reperfusion. The plasma glucose level was significantly higher in diabetic rats com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 33 publications
4
23
0
1
Order By: Relevance
“…In addition, higher I/R injury and corresponding less IPC‐mediated protection in DCM, when compared with the DM heart in the present study, account for the influence of metabolic changes induced by an HFD that induced structural changes in the myocardium. In agreement with the previous preclinical trial, [ 34 ] DM heart showed comparatively less infarct size and better hemodynamics than normal and DCM heart, emphasizing the infarct sparing effect of DM against I/R.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, higher I/R injury and corresponding less IPC‐mediated protection in DCM, when compared with the DM heart in the present study, account for the influence of metabolic changes induced by an HFD that induced structural changes in the myocardium. In agreement with the previous preclinical trial, [ 34 ] DM heart showed comparatively less infarct size and better hemodynamics than normal and DCM heart, emphasizing the infarct sparing effect of DM against I/R.…”
Section: Discussionsupporting
confidence: 92%
“…The metabolic features manifested in this animal model are in many ways similar to the pathogenesis of inherited spontaneous T2DM in humans [ 29 , 32 ]. However, hyperglycemia and glucose intolerance developed in GK rats are not associated with the development of obesity or hypertension [ 1 ]. The adult GK rat of T2DM has been shown to develop cardiovascular complications including left ventricular hypertrophy, fibrosis, as well as diastolic and/or systolic dysfunction [ 1 , 20 , 35 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Diabetes mellitus is a heterogeneous chronic metabolic disorder characterized by hyperglycemia as a common feature resulting from impaired insulin secretion, insulin resistance, or both [ 1 ]. In 2014, the global prevalence of diabetes mellitus (DM) was estimated to be 9 % among adults according to WHO data [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last decades, diabetes mellitus (DM) has aroused increasing attention globally 1 . Ischemic heart disease is a major cardiovascular complication of diabetes and the primary cause of mortality in diabetic disease 2 . A number of studies have confirmed that compared with non-diabetic patients, patients with diabetes were susceptible to myocardial ischemia-reperfusion injury, and have poor treatment effect 3 .…”
Section: ■ Introductionmentioning
confidence: 99%